2006
DOI: 10.1111/j.1365-2958.2006.05313.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the apo‐PerR‐Zn protein from Bacillus subtilis

Abstract: SummaryBacteria adapt to elevated levels of Reactive Oxygen Species (ROS) by increasing the expression of defence and repair proteins, which is regulated by ROS responsive transcription factors. In Bacillus subtilis the zinc protein PerR, a peroxide sensor that binds DNA in the presence of a regulatory metal Mn 2+ or Fe 2+, mediates the adaptive response to H2O2. This study presents the first crystal structure of apoPerR-Zn which shows that all four cysteine residues of the protein are involved in zinc co-ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(158 citation statements)
references
References 44 publications
8
148
2
Order By: Relevance
“…3A). Metal binding to the sensor site promotes a change in PerR conformation from an extended to a more compact form that binds promoter DNA (5,6). The metal-binding-promoted change of PerR to the compact conformation is explained by the fact that H37 and H91, both of which participate directly as metal binding, are located in the two different domains of PerR; thus, these residues can help bring the two PerR domains in each monomer in close proximity and stabilize the compact form.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Metal binding to the sensor site promotes a change in PerR conformation from an extended to a more compact form that binds promoter DNA (5,6). The metal-binding-promoted change of PerR to the compact conformation is explained by the fact that H37 and H91, both of which participate directly as metal binding, are located in the two different domains of PerR; thus, these residues can help bring the two PerR domains in each monomer in close proximity and stabilize the compact form.…”
Section: Resultsmentioning
confidence: 99%
“…The other resides in the Ddomain, constructed by either four conserved cysteines near the C terminus (C-site) or residues at the surface of the D-domain pointing toward the hinge region (D-site). Structural comparison between inactive apo-and metallated active forms of BsPerR suggested that regulatory metal binding causes DB-domains to swing around the hinge region with respect to the D-domain, from an open (swung-out) to closed (converged) conformations (22)(23)(24). This process leads to a model that the rearrangement of DBdomains by binding a regulatory metal in the hinge region is responsible for the allosteric transition of all Fur family regulators, from the inactive open conformation to the active closed one (23).…”
mentioning
confidence: 99%
“…1). 10,[12][13]15 To investigate the role of structural Zn 2+ site in peroxide sensing by His oxidation, mutant proteins altered in any of the four cysteine residues were analyzed by MALDI-TOF MS as described above. All the cysteine to serine substitution mutant proteins (C96S, C99S, C136S, C139S) exhibited no detectable oxidation of either T5 containing H37 or T11 containing H91 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). 15 In the absence of regulatory metal ion, the apo-PerR (PerR:Zn) adopts a rather flat conformation, where the two DNA-binding domains project opposite directions from the dimerization domain (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%